Preparation method of modified nanoparticle-acrylamide copolymerized anti-scouring flocculant
By using modified nanoparticle-acrylamide copolymerized hyperbranched polymer as flocculant, the problem of poor dispersion resistance of existing flocculants under high flow velocity water flow erosion is solved, and concrete is realized under high flow velocity environment Good anti-shrink and dispersion properties while maintaining good fluidity.
Patent Information
- Application Number
- CN202411533477.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-11
AI Technical Summary
When existing flocculants that do not disperse underwater concrete are flushed against water flow at higher flow rates, the anti-dispersion effect is average, and increasing the amount of flocculant will cause the concrete to be too viscous and difficult to construct.
The modified nanoparticle-acrylamide copolymerized hyperbranched polymer is used as the flocculant and synthesized by aqueous solution polymerization method, which significantly improves the anti-shrinkage and dispersion properties of concrete under a certain velocity of water flow, and also has a certain water reduction effect to improve The flow of concrete.
It significantly improves the anti-shrinkage and dispersion properties of concrete mixture under a certain velocity of water flow, has good fluidity, meets construction conditions, and reduces engineering costs.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the field of concrete, and in particular to a method for preparing a modified nanoparticle-acrylamide copolymer anti-scour flocculant. Background Art
[0002] As the most commonly used civil engineering material, concrete is widely used in the construction of hydraulic structures such as bridges, docks, revetments, and drilling platforms. When ordinary concrete is directly poured underwater, it will be affected by water and will cause separation, cement loss, strength reduction, and environmental pollution. Therefore, cofferdam isolation method, conduit method, bag stacking method, open-bottom bucket method, pumping method and other pouring methods are usually used to solve the problem of underwater concrete pouring from a construction perspective. However, the use of the above methods for construction will complicate the process to a certain extent, prolong the construction period, and thus increase the project cost.
[0003] In this context, scholars have developed an underwater non-dispersible concrete. By adding flocculants to the concrete, the components are made to stick together, so that it can be directly poured in the water without dispersion and segregation. It is called the "new generation of underwater engineering materials". At present, the commonly used flocculants for underwater non-dispersible concrete are cellulose and polyacrylamide. In some special construction areas such as the tailwater impact area of the hydropower plant, the coastal tidal range water level change area, and the river channel with a certain flow rate, the newly poured non-dispersible concrete needs to withstand the scouring of water flow at a certain speed before it hardens. The commonly used flocculants are all developed in a static water environment and are only suitable for static water or relatively small water flow environments. When faced with high-speed water flow scouring, these flocculants have a general anti-dispersion effect. Although the anti-dispersion can be improved by increasing the amount of flocculants, it will cause the concrete to be too viscous, difficult to construct, and the setting time is too long.
[0004] Aiming at the problem that the currently commonly used flocculants are not sufficient to enable underwater non-dispersible concrete mixtures to overcome the scouring of water flow at a certain speed, the present invention, based on the research of traditional organic polyacrylamide flocculants, introduces inorganic component-modified nanoparticles to synthesize an inorganic-organic hybrid hyperbranched polymer, which changes the linear structure of the original polyacrylamide molecules, has strong shear resistance, and significantly improves the anti-scouring ability of concrete mixtures under water flow at a certain speed. Summary of the invention
[0005] Aiming at the problem that the currently commonly used cellulose-based and polyacrylamide-based flocculants cannot make underwater non-dispersible concrete mixtures resist the scouring of water flow at a certain speed, the present invention uses acrylamide and acrylic acid as organic monomers and modified nanoparticles as inorganic monomers to synthesize a modified nanoparticle-acrylamide copolymerized hyperbranched polymer by aqueous solution polymerization. The prepared flocculant can significantly improve the concrete mixture's ability to resist the scouring of water flow at a certain speed and its anti-dispersion performance, and at the same time has a certain water-reducing effect, and can improve the fluidity of concrete.
[0006] In order to achieve the above-mentioned purpose and advantages of the present invention, a method for preparing a modified nano-silica-acrylamide copolymer anti-scour flocculant is provided, comprising the following steps:
[0007] 1) Weigh the silane coupling agent and dissolve it in ethanol aqueous solution, stir for 20 to 30 minutes to obtain the silane coupling agent hydrolyzate. Weigh the nanoparticles and dissolve them in ethanol aqueous solution, ultrasonicate for 20 to 40 minutes, raise the temperature to 60 to 70°C, and slowly drop the silane coupling agent hydrolyzate. React for 6 to 8 hours, wash the product with ethanol, dry it, and grind it to obtain the modified nanoparticle powder.
[0008] 2) Dissolve inorganic monomer-modified nanoparticles, organic monomers acrylamide and acrylic acid in deionized water, stir for 20 to 30 minutes, and ultrasonicate for 20 to 40 minutes. Adjust the pH of the aqueous solution to 8 to 9 with sodium hydroxide solution, and add a small amount of deionized water to adjust the total mass concentration of the monomers.
[0009] 3) Adding a complexing agent, a chain transfer agent and urea to the aqueous solution obtained in 2) in sequence, stirring for 30 minutes, raising the temperature to 35° C., and continuously introducing nitrogen to deoxygenate for 30 minutes.
[0010] 4) Using a dropping funnel, slowly add measured amounts of redox initiators ammonium persulfate, sodium bisulfite and azo initiator azobisisobutylamidine to the solution obtained in 3), stir evenly, and continue to introduce nitrogen protection until the system becomes noticeably viscous.
[0011] 5) Seal the three-necked flask and keep it at a constant temperature for 4 hours. Purify the product with anhydrous ethanol and wash it repeatedly until it turns white and the hardness increases, and then granulate, dry and grind it.
[0012] The preparation method of the modified nanoparticle-acrylamide copolymer anti-scouring flocculant of the present invention is characterized in that the nanoparticles are selected from one of nano-silicon dioxide, nano-titanium dioxide, nano-calcium carbonate and nanoparticles with similar composition structures. The common characteristics of the selected nanoparticles are that they contain a large number of hydroxyl groups on the surface, are hydrophilic, have good chemical activity, but are easy to agglomerate. Modifying the nanoparticles can, on the one hand, prevent the nanoparticles from agglomerating, so that they can be evenly dispersed in the polymer matrix; on the other hand, the nanoparticles can be grafted with carbon-carbon double bonds, so that they can form not only weak hydrogen bonds with organic monomers during polymerization, but also stronger covalent bonds, effectively avoiding the phenomenon of macroscopic two-phase interface separation of conventional inorganic-organic composite flocculants under the shear force of water flow. The higher the degree of modification of the nanoparticles, the more branches there are, and the higher the strength of the three-dimensional network formed by mutual entanglement; and the formed molecular chains are more contracted, and the branches are less destroyed under the same shear force, which is finally reflected in the better water flow scouring resistance of the concrete. However, as the degree of modification increases, too many branches easily cause the molecular chains to entangle too quickly and become chaotic, which is manifested in the rapid loss of slump of the mixture, which is not conducive to actual construction. The present invention controls the degree of modification of nanoparticles within 60-80%, which can effectively balance the anti-scourability and fluidity of the mixture.
[0013] To optimize the above steps, specific measures taken also include:
[0014] In step 1), the volume ratio of ethanol to water in the ethanol-water solution is 3:1, the mass ratio of the nanoparticles to the silane coupling agent is 1:(0.1-0.3), and the concentration of the nanoparticles is 0.5wt.%-1wt.%.
[0015] In step 1), the modification degree of the modified nanoparticles is 60% to 80%.
[0016] In step 2), the molar ratio of the organic monomers acrylamide and acrylic acid is (3-4):1, the modified nanoparticles account for 0.5%-2.5% of the total mass of the monomers, the concentration of the sodium hydroxide solution is 0.1-1 mol / L, and the total mass concentration of the monomers is 23%-28%.
[0017] In step 3), the weight of the complexing agent is 0.01% to 0.02% of the total weight of the monomers, the weight of the chain transfer agent is 0.01% to 0.02% of the total weight of the monomers, and the weight of the urea is 1.1% to 1.3% of the total weight of the monomers.
[0018] In step 4), the molar ratio of the oxidizing agent ammonium persulfate to the reducing agent sodium bisulfite is 1:1, the mass ratio of the redox initiator to the azo initiator is 1:3, and the total mass of the initiator is 0.2% to 0.35% of the total mass of the monomers.
[0019] The beneficial effects of the present invention are:
[0020] (1) The flocculant prepared by the present invention can effectively improve the ability of concrete mixture to resist water scouring at a certain speed. The hyperbranched polymer described in the present invention has modified nanoparticles as the core and organic polymers as the side chains to form a star-shaped structure. Due to the relatively linear structure of ordinary polyacrylamide flocculant molecules, the network structure formed between molecules is weakly connected and the interaction force is small. Under the action of the shear force of the water flow, the interaction force between molecules is destroyed and the molecular chain breaks from the middle, resulting in a loss of anti-dispersion, so that it is not enough to restrain the components on the concrete surface that are in contact with water, the concrete surface is scoured, and the coarse aggregate is exposed. However, the molecular side chains of hyperbranched polymers are more, and the molecules are easy to interact and entangle with each other to form a certain network structure, and the strength of the formed network structure is relatively high. When subjected to the shear force of water flow, the intermolecular force is strong and not easily dispersed, and the star-shaped structure will only break part of the side chains under the shear force, retaining most of the molecular weight and viscosity of the main molecular chain, which is manifested in that the anti-dispersion loss of the freshly mixed concrete is small, and the bonding ability of the contact surface between concrete and water is not greatly affected by the shear force of water flow, thereby effectively resisting the erosion of water flow at a certain flow rate.
[0021] (2) The flocculant prepared by the present invention can make the concrete mixture have excellent anti-dispersion and fluidity that meets construction conditions. Compared with ordinary polyacrylamide flocculant molecules, the flocculant of the present invention is a star-shaped structure of a hyperbranched polymer molecule with a larger specific surface area, an obvious three-dimensional network, a stronger bridging ability, and is easier to adsorb particles, showing a better anti-dispersion effect. When ordinary polyacrylamide flocculants are used, the concrete mixture will have problems such as high viscosity and difficulty in construction, rapid slump loss, and relatively low water and land strength. The flocculant of the present invention uses acrylic acid as one of the organic monomers, and the carboxyl group (-COOH) it contains is a water-reducing group, which can effectively improve the fluidity of the concrete mixture. The molar ratio of the organic components acrylamide and acrylic acid in the flocculant of the present invention is controlled at (3-4):1, and the mixture has good anti-scouring and anti-dispersion capabilities and slump retention performance that meets construction conditions. Compared with traditional polyacrylamide flocculant molecules, the hyperbranched polymer molecules of the present invention have more side chains and less freedom, which can enhance the solvation binding ability of mixing water on the one hand, and leave some unbound free water in the mixture on the other hand. When the flocculant molecules adsorb concrete particles, a protective layer will be formed on the surface of the particles to inhibit cement hydration, and free water will flow between the wrapped cement particles at this time, reducing the friction between the particles, thereby improving the collapse resistance of the concrete. The hyperbranched polymer of the present invention uses nano-silicon dioxide as the core, has a more regular structure, has a certain steric hindrance, and is conducive to increasing the fluidity of the concrete mixture.
[0022] (3) The present invention selects nanoparticles as the core of the hyperbranched polymer. Compared with most synthesis methods using organic matter as the core, the number of branches is more controllable, the regularity of the core is better, and the production cost is lower. DETAILED DESCRIPTION
[0023] The present invention will be further described below in conjunction with the embodiments.
[0024] Example 1
[0025] A method for preparing a modified nano-silica-acrylamide copolymer anti-scour flocculant comprises the following steps:
[0026] Weigh vinyl triethoxysilane and dissolve it in ethanol aqueous solution, stir for 30 minutes to obtain vinyl triethoxysilane hydrolyzate. Weigh nano silicon dioxide and dissolve it in ethanol aqueous solution, ultrasonicate for 40 minutes, raise the temperature to 70°C, and slowly drop vinyl triethoxysilane hydrolyzate. React for 6 hours, wash the product with ethanol, dry and grind it to obtain modified nano silicon dioxide powder.
[0027] Dissolve inorganic monomer modified nano-silica, organic monomer acrylamide and acrylic acid in deionized water, stir for 30 minutes, and ultrasonicate for 40 minutes. Use 1 mol / L sodium hydroxide solution to adjust the pH of the aqueous solution to 8.5, and add a small amount of deionized water to adjust the total mass concentration of the monomer. Add complexing agent EDTA-2Na, chain transfer agent HCOONa and urea to the reaction vessel, stir for 30 minutes, raise the temperature to 35°C, and continue to pass nitrogen to deoxygenate for 30 minutes. Slowly add the measured redox initiator ammonium persulfate, sodium bisulfite and azo initiator azobisisobutylamidine to the reaction vessel with a dropping funnel, stir evenly, and continue to pass nitrogen protection until the system is obviously viscous. Seal the three-necked flask and keep it at a constant temperature for 4 hours. The product is purified with anhydrous ethanol and washed repeatedly until it turns white and the hardness increases, and then granulated, dried and crushed to obtain SiO2-P (AM-AA), a flocculant for underwater non-dispersible concrete. The mass ratio of nano silicon dioxide, vinyl triethoxysilane, acrylamide, acrylic acid, ammonium persulfate, sodium bisulfite and azobisisobutylamidine is 0.7:0.2:100:34:0.05:0.02:0.2.
[0028] Example 2
[0029] A method for preparing a modified nano titanium dioxide-acrylamide copolymer anti-scour flocculant comprises the following steps:
[0030] Weigh vinyl triethoxysilane and dissolve it in ethanol aqueous solution, stir for 30 minutes to obtain vinyl triethoxysilane hydrolyzate. Weigh nano titanium dioxide and dissolve it in ethanol aqueous solution, ultrasonicate for 40 minutes, raise the temperature to 70°C, and slowly drop vinyl triethoxysilane hydrolyzate. React for 6 hours, wash the product with ethanol, dry it, and grind it to obtain modified nano titanium dioxide powder.
[0031] The inorganic monomer modified nano titanium dioxide, organic monomer acrylamide and acrylic acid are dissolved in deionized water, stirred for 30 minutes, and ultrasonicated for 40 minutes. The pH of the aqueous solution is adjusted to 8.5 with 1 mol / L sodium hydroxide solution, and a small amount of deionized water is added to adjust the total mass concentration of the monomer. The complexing agent EDTA-2Na, the chain transfer agent HCOONa and urea are added to the reaction vessel, stirred for 30 minutes, the temperature is raised to 35°C, and nitrogen is continuously introduced for deoxygenation for 30 minutes. The dropping funnel slowly drips the measured redox initiator ammonium persulfate, sodium bisulfite and azo initiator azobisisobutylamidine into the reaction vessel, stirs evenly, and continuously introduces nitrogen protection until the system is obviously viscous. The three-necked flask is sealed and kept at a constant temperature for 4 hours. The product is purified with anhydrous ethanol and repeatedly washed until it turns white and the hardness increases, and then granulated, dried and crushed to obtain the flocculant TiO2-P (AM-AA) for underwater non-dispersible concrete. The mass ratio of nano titanium dioxide, vinyl triethoxysilane, acrylamide, acrylic acid, ammonium persulfate, sodium bisulfite and azobisisobutylamidine is 1.2:0.4:100:34:0.05:0.02:0.2.
[0032] Comparative Example 1
[0033] Anionic polyacrylamide PAM with a molecular weight of 12 million is a commercially available product.
[0034] Comparative Example 2
[0035] The propylene-based flocculant model is UWB-II, which is a commercially available product.
[0036] Comparative Example 3
[0037] Weigh vinyl triethoxysilane and dissolve it in ethanol aqueous solution, stir for 30 minutes to obtain vinyl triethoxysilane hydrolyzate. Weigh nano silicon dioxide and dissolve it in ethanol aqueous solution, ultrasonicate for 40 minutes, raise the temperature to 70°C, and slowly drop vinyl triethoxysilane hydrolyzate. React for 6 hours, wash the product with ethanol, dry and grind it to obtain modified nano silicon dioxide powder.
[0038] Dissolve acrylamide and acrylic acid in deionized water, stir for 30 minutes, and ultrasonicate for 40 minutes. Use 1 mol / L sodium hydroxide solution to adjust the pH of the aqueous solution to 8.5, and add a small amount of deionized water to adjust the total mass concentration of the monomer. Add complexing agent EDTA-2Na, chain transfer agent HCOONa and urea to the reaction vessel, stir for 30 minutes, raise the temperature to 35°C, and continue to pass nitrogen to deoxygenate for 30 minutes. Use a dropping funnel to slowly add the measured redox initiator ammonium persulfate, sodium bisulfite and azo initiator diisobutylamidine to the reaction vessel, stir evenly, and continue to pass nitrogen protection until the system is obviously viscous. Seal the three-necked flask and let it stand at a constant temperature for 4 hours. Purify the product with anhydrous ethanol and wash it repeatedly until it turns white and the hardness increases, then granulate, dry and crush it to obtain the organic flocculant P (AM-AA). The mass ratio of acrylamide, acrylic acid, ammonium persulfate, sodium bisulfite and azobisisobutylamidine is 100:34:0.05:0.02:0.2. The modified nano-silicon dioxide powder and the synthesized organic flocculant P (AM-AA) are uniformly mixed at a mass ratio of 0.005:1 to obtain a SiO2+P (AM-AA) flocculant.
[0039] Comparative Example 4
[0040] Weigh vinyl triethoxysilane and dissolve it in ethanol aqueous solution, stir for 30 minutes to obtain vinyl triethoxysilane hydrolyzate. Weigh nano titanium dioxide and dissolve it in ethanol aqueous solution, ultrasonicate for 40 minutes, raise the temperature to 70°C, and slowly drop vinyl triethoxysilane hydrolyzate. React for 6 hours, wash the product with ethanol, dry it, and grind it to obtain modified nano titanium dioxide powder.
[0041] Dissolve acrylamide and acrylic acid in deionized water, stir for 30 minutes, and ultrasonicate for 40 minutes. Use 1 mol / L sodium hydroxide solution to adjust the pH of the aqueous solution to 8.5, and add a small amount of deionized water to adjust the total mass concentration of the monomer. Add complexing agent EDTA-2Na, chain transfer agent HCOONa and urea to the reaction vessel, stir for 30 minutes, raise the temperature to 35°C, and continue to pass nitrogen to deoxygenate for 30 minutes. Use a dropping funnel to slowly add the measured redox initiator ammonium persulfate, sodium bisulfite and azo initiator diisobutylamidine to the reaction vessel, stir evenly, and continue to pass nitrogen protection until the system is obviously viscous. Seal the three-necked flask and let it stand at a constant temperature for 4 hours. Purify the product with anhydrous ethanol and wash it repeatedly until it turns white and the hardness increases, then granulate, dry and crush it to obtain TiO2-P (AM-AA), a flocculant for underwater non-dispersible concrete. The mass ratio of acrylamide, acrylic acid, ammonium persulfate, sodium bisulfite and azobisisobutylamidine is 100:34:0.05:0.02:0.2. The modified nano titanium dioxide powder and the synthesized organic flocculant P (AM-AA) are uniformly mixed at a mass ratio of 0.009:1 to obtain a TiO2+P (AM-AA) flocculant.
[0042] Implementation effect verification:
[0043] The flocculants for underwater non-dispersible concrete prepared in Examples 1 and 2 of the present invention were added to concrete, and the flowability, anti-dispersion and anti-scouring properties were measured and compared with the concrete properties mixed with the comparative examples of PAM and UWB-II flocculants. The flowability is characterized by the degree of expansion, the anti-dispersion performance is characterized by the turbidity value and pH value measured in accordance with DL / T 5117-2000 "Test Procedures for Underwater Non-dispersible Concrete", and the anti-scouring performance is characterized by the maximum water flow velocity that the freshly mixed concrete can withstand under controlled water flow without exposing the aggregates, that is, the limiting flow velocity. The concrete mix ratio used in the experiment is: cement 500kg / m 3 , 5-25mm continuous graded crushed stone 1026kg / m 3 , river sand with fineness modulus of 2.46 684kg / m 3 , polycarboxylate water reducer 4.5kg / m 3 , water 190kg / m 3 The dosage of PAM and UWB-II flocculants is 1% and 2.5% of the concrete mass respectively according to experience. The test results are shown in Table 1 below.
[0044] Table 1 Test results
[0045]
[0046]
[0047] It can be seen from the results in Table 1 that the flocculants prepared in Examples 1 and 2 of the present invention not only have a lower dosage, but also have good anti-dispersion properties of the obtained concrete and fluidity that meets construction requirements, and compared with Comparative Examples 1 and 2, the anti-scouring performance of the concrete under dynamic water is significantly improved.
[0048] Specifically, as the amount of SiO2-P (AM-AA) flocculant increases, the fluidity of the concrete shows a downward trend, while the anti-dispersion and water scouring resistance show an upward trend. By comparing with the experimental data of Comparative Examples 1 and 2, it can be found that the various properties of the SiO2-P (AM-AA) flocculant at a dosage of 0.5% have reached the level of UWB-II flocculant, and are better than PAM flocculant; the anti-scouring performance of the SiO2-P (AM-AA) flocculant at a dosage of 1% is significantly higher than that of UWB-II and PAM flocculants. When the dosage of SiO2-P (AM-AA) flocculant is 1-1.5%, the anti-scouring performance improvement effect is not obvious, and the fluidity is poor when the dosage is 1.5%. Therefore, when the dosage of SiO2-P (AM-AA) flocculant is about 1%, the concrete has good fluidity, anti-dispersion and anti-scouring performance. By comparing with the experimental data of comparative example 3, it can be found that under the premise of the same dosage, the anti-dispersion of SiO2-P (AM-AA) flocculant is slightly higher than that of the modified SiO2 and P (AM-AA), the fluidity is slightly lower, and the anti-scouring performance is significantly improved. From the perspective of molecular structure, the SiO2+P (AM-AA) flocculant only uniformly mixes the polymer P (AM-AA) and the modified nano-silicon dioxide, and its molecules are linear polymer structures. Under the shearing action of the water flow, the molecular chain breaks and loses the binding force on the various components of the concrete. Therefore, the limit flow rate is similar to that of comparative examples 1 and 2. Even if nano-silicon dioxide is added, the anti-scouring performance of the concrete under water cannot be improved; and the SiO2-P (AM-AA) flocculant forms a hyperbranched polymer with nano-silicon dioxide as the core because the modified nano-silicon dioxide participates in the polymerization reaction. The special star-shaped structure of the molecule effectively improves the anti-scouring performance of the underwater non-dispersible concrete. When the dosage of SiO2-P (AM-AA) flocculant is 0.5-1%, the anti-dispersion effect is not much different from that of UWB-II flocculant, but the anti-scouring performance is significantly improved, which further explains that the anti-scouring mechanism of SiO2-P (AM-AA) flocculant is not due to the increase in dosage, which leads to improved anti-dispersion and thus improved anti-scouring performance, but because SiO2-P (AM-AA) flocculant is a hyperbranched polymer with strong intermolecular forces and a large number of molecular branches. Under the shear force of water, only a small number of branches will be broken, thereby retaining most of the molecular weight and viscosity of the flocculant molecules.
[0049] Specifically, the fluidity of TiO2-P (AM-AA) flocculant meets the construction requirements; the anti-dispersion is slightly lower than that of SiO2-P (AM-AA) flocculant, better than that of PAM flocculant, and is not much different from that of UWB-II flocculant at a dosage of 1% and 1.5%; the anti-scouring is lower than that of SiO2-P (AM-AA) flocculant, but still better than that of PAM and UWB-II flocculants. Compared with comparative example 4 with the same dosage, it is also found that the limiting flow velocity of TiO2-P (AM-AA) flocculant is significantly improved, proving that the anti-scouring mechanism of TiO2-P (AM-AA) flocculant is similar to that of SiO2-P (AM-AA) flocculant, both of which are due to its unique star-shaped molecular structure.
[0050] From the test results of the embodiments and comparative examples, the modified nanoparticle-acrylamide copolymer anti-scour flocculant proposed in the present invention has the ability to improve the anti-scour property of underwater non-dispersible concrete in moving water, and has good anti-dispersion and fluidity that meets construction conditions.
Claims
1. A method for preparing a modified nanoparticle-acrylamide copolymer anti-scour flocculant, characterized in that: The following steps are involved: 1) weighing a silane coupling agent and dissolving it in an ethanol aqueous solution, stirring for 20 to 30 minutes to obtain a silane coupling agent hydrolyzate, weighing nanoparticles and dissolving them in an ethanol aqueous solution, ultrasonicating for 20 to 40 minutes, raising the temperature to 60 to 70° C., and slowly dropping the silane coupling agent hydrolyzate, reacting for 6 to 8 hours, washing the product with ethanol, drying, and grinding to obtain a modified nanoparticle powder; 2) dissolving inorganic monomer-modified nanoparticles, organic monomers acrylamide and acrylic acid in deionized water, stirring for 20 to 30 minutes, ultrasonicating for 20 to 40 minutes, adjusting the pH of the aqueous solution to 8 to 9 with sodium hydroxide solution, and adding a small amount of deionized water to adjust the total mass concentration of the monomers; 3) adding a complexing agent, a chain transfer agent and urea to the aqueous solution obtained in 2) in sequence, stirring for 30 minutes, raising the temperature to 35° C., and continuously introducing nitrogen to deoxygenate for 30 minutes; 4) Slowly add the measured redox initiator ammonium persulfate, sodium bisulfite and azo initiator azobisisobutylamidine to the solution obtained in 3) using a dropping funnel, stir evenly, and continue to introduce nitrogen protection until the system is obviously viscous; 5) Seal the three-necked flask and let it stand at a constant temperature for 4 hours. Purify the product with anhydrous ethanol and wash it repeatedly until it turns white and the hardness increases. Then granulate, dry and grind it.
2. The method for preparing the modified nanoparticle-acrylamide copolymer anti-scour flocculant according to claim 1, characterized in that: The nanoparticles are selected from one of nano silicon dioxide, nano titanium dioxide and nano calcium carbonate.
3. The method for preparing the modified nanoparticle-acrylamide copolymer anti-scour flocculant according to claim 1, characterized in that: In step 1), the volume ratio of ethanol to water in the ethanol-water solution is 3:1, the mass ratio of the nanoparticles to the silane coupling agent is 1:(0.1-0.3), and the concentration of the nanoparticles is 0.5wt.%-1wt.%.
4. The method for preparing the modified nanoparticle-acrylamide copolymer anti-scour flocculant according to claim 1, characterized in that: In step 1), the modification degree of the modified nanoparticles is 60% to 80%.
5. The method for preparing the modified nanoparticle-acrylamide copolymer anti-scour flocculant according to claim 1, characterized in that: In step 2), the molar ratio of the organic monomers acrylamide and acrylic acid is (3-4):1, the modified nanoparticles account for 0.5%-2.5% of the total mass of the monomers, the concentration of the sodium hydroxide solution is 0.1-1 mol / L, and the total mass concentration of the monomers is 23%-28%.
6. The method for preparing the modified nanoparticle-acrylamide copolymer anti-scour flocculant according to claim 4, characterized in that: The total mass of the monomers is the sum of the masses of the inorganic monomer-modified nano-silicon dioxide particles and the organic monoacrylamide and acrylic acid.
7. The method for preparing the modified nanoparticle-acrylamide copolymer anti-scour flocculant according to claim 1, characterized in that: In step 3), the weight of the complexing agent is 0.01% to 0.02% of the total weight of the monomers, the weight of the chain transfer agent is 0.01% to 0.02% of the total weight of the monomers, and the weight of the urea is 1.1% to 1.3% of the total weight of the monomers.
8. The method for preparing the modified nanoparticle-acrylamide copolymer anti-scour flocculant according to claim 1, characterized in that: In step 4), the molar ratio of the oxidizing agent ammonium persulfate to the reducing agent sodium bisulfite is 1:1, the mass ratio of the redox initiator to the azo initiator is 1:3, and the total mass of the initiator is 0.2% to 0.35% of the total mass of the monomers.
Citation Information
Patent Citations
Modified polyacrylamide for concrete as well as preparation method and application of modified polyacrylamide
CN118459656A
Flocculant of cation of millicron SiOx compound polyacrylamide and preparing method thereof
CN1500740A
Cited By
Special flying prevention auxiliary agent for cigars as well as preparation method and application of special flying prevention auxiliary agent
CN120078016A